Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.techfore.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Aligning university–industry interactions: The role of boundary spanning in intellectual capital transfer

Abstract: Abstract:In the UK, the boundary spanning role has taken on greater significance as successive governments emphasize how universities should play in direct knowledge transfer and changing academics' visions over third mission functions. Studies in the UK have focused on the relative performance of technology transfer organizations (TTOs) / knowledge transfer organizations (KTOs) or their use by academics and external organizations. Compared to their US and international counterparts, TTOs/KTOs at UK universiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 50 publications
1
36
0
8
Order By: Relevance
“…The transfer process would also include the tacit knowledge and experience (i.e., intangible components) stored within the individuals involved in creating and transferring the technology (Muthusamy and White, ), because technology and its knowledge base are typically inseparable (Bozeman et al, ). However, and despite the progress in this field, many studies show that technology transfer process in a UIC setting is actually complex and fraught with execution‐related difficulties and challenges, which can lead to suboptimal output (Perkmann et al, ; Chau et al, ; Miller et al, ). Seeking to unpack the complexity of this process, research has identified some critical factors that influence the effectiveness of technology transfer (Shane et al, ), including technology characteristics (e.g., ‘articulability’ and ‘appropriability’); actors’ perceived difficulty, compatibility, and observed benefit; technological uncertainty and inexperience (deficit in tacit knowledge to deal with the new technology); business newness (inability to commercialize innovation); and high upfront cost of the technology (Bruneel et al, ; Yang et al, ; Fernández‐Esquinas et al, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer process would also include the tacit knowledge and experience (i.e., intangible components) stored within the individuals involved in creating and transferring the technology (Muthusamy and White, ), because technology and its knowledge base are typically inseparable (Bozeman et al, ). However, and despite the progress in this field, many studies show that technology transfer process in a UIC setting is actually complex and fraught with execution‐related difficulties and challenges, which can lead to suboptimal output (Perkmann et al, ; Chau et al, ; Miller et al, ). Seeking to unpack the complexity of this process, research has identified some critical factors that influence the effectiveness of technology transfer (Shane et al, ), including technology characteristics (e.g., ‘articulability’ and ‘appropriability’); actors’ perceived difficulty, compatibility, and observed benefit; technological uncertainty and inexperience (deficit in tacit knowledge to deal with the new technology); business newness (inability to commercialize innovation); and high upfront cost of the technology (Bruneel et al, ; Yang et al, ; Fernández‐Esquinas et al, ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example, Das and Teng () argued that, in addition to helping set the direction for the alliance, clear objectives also facilitate the institution of specific rules and regulations, which are important for formal control mechanisms. Importantly, these objectives would specify what is expected of partners, and thus make it easier for the partners to identify the activities to engage with in order to exploit their learning potential (Chau et al, ).…”
Section: Social Capital and Technology Transfer: Toward An Integrativmentioning
confidence: 99%
“…Review articles, as in Cunningham et al (2017), have developed qualitative methods for researching technology transfer. Chau et al (2017) sought to justify the low performance of the United Kingdom against the knowledge and technology transfer of organizations. Dubickis and Gaile-Sarkane (2017) reviewed the literature for the tacit dichotomy against explicit knowledge.…”
Section: Technology Transfer and Knowledge Management Overlapmentioning
confidence: 99%
“…The social and economic benefits of academia such as training personnel, scientific knowledge transfer, and creating an infrastructure contributes to industrial innovation (Cohen et al, 2002;Elder, 2018). Academia feels dependency on the industrial sector for its knowledge economy, research & development, scientific approach, patenting (Nelson, 2001), academic entrepreneurship, (Shane, 2007), technology transfer, and collaboration centers (Chau et al, 2017;Nelson, 2001;Shane, 2007) and accordingly, it is hypothesized that;…”
Section: Antecedents Of Academiamentioning
confidence: 99%